PENGARUH SOSIALISASI SISTEM IMBALAN RANCANGAN ROWAN TERHADAP PERSEPSI MENGENAI SISTEM IMBALAN DAN MOTIVASI KERJA KARYAWAN BAGIAN PRODUKSI DI PT. X. YOGYAKARTA - Nopita, Nopita; Rosyid, Haryanto Fadholan; Nashori, Fuad (Jurnal Ilmiah IKIP Mataram, 2018)
This study aims to gain a clear reward system design in increasing positive perceptions of the reward system and see its effect on work motivation, the next goal to saw the relationship between perception and motivation. The hypothesis proposed in this study is the positive influence perceptions of the reward system for employee motivation and significant relationship between perceptions of the reward system to motivate employees. The subject of the study amounted to 12 respondents were taken from the classical employees of the production unit of Damai workshop. This study uses three variables namely socialization research Rowan plan design reward system, perceptions of the reward system and employee motivation. The method of research was done by using an experimental one group pretest-posttest design. Measurement of perception and motivation using a questionnaire, given both before and after the intervention in the form of socialization of Rowan plan design reward system. Assessment measure using point numbers consist of 1 to 5 points on each statement. The results of data analysis using the non-parametric statistical difference test Sign test method showed no differences in perceptions and motivation before and after a given socialization reward system, it can be seen from the value of the sign (-) totaling 3 h = 2 ie 3> 2 the indicates the null hypothesis is rejected. As for the second test of the hypothesis that the relationship between the variables with the perception of work motivation, looks count rs > rs table (0.782> 0.591) with Î± = 0.05, which means there is a strong positive relationship between the variables with the variable perception of work motivation.